A transcribed ultraconserved noncoding RNA, uc.417, serves as a negative regulator of brown adipose tissue thermogenesis. Issue 12 (21st September 2016) - Cui, Xianwei; You, Lianghui; Li, Yun; Zhu, Lijun; Zhang, Fan; Xie, Kaipeng; Cao, Yan; Ji, Chenbo; Guo†, Xirong
ABSTRACT: Brown adipose tissue (BAT) oxidizes fatty acids for thermogenesis and could therefore be considered as part of a new strategy in combating obesity and associated metabolic diseases. It is well established that aging is accompanied by a decline of brown adipocyte regenerative capacity. How aging contributes to this loss is poorly understood. Here, we identify a long noncoding RNA, uc.417, which is transcribed from an ultraconserved region in rodents. Expression of uc.417 increases with age. Ectopic expression of uc.417 impairs adipogenesis and the thermogenic program in brown adipocytes. However, uc.417 is not required for brown fat function. In vivo, uc.417 attenuates the cold‐induced thermogenic programin mouse BAT. Moreover, we find that uc.417 moderately inhibits phosphorylation of p38MAPK without affecting the total protein level of p38MAPK. The p38MAPK pathway is essential for activating BAT to stimulate uncoupling protein 1 gene expression. The data point to uc.417 as being an important factor in an age‐dependent loss of function of brown adipose tissue.—Cui, X., You, L., Li, Y., Zhu, L., Zhang, F., Xie, K., Cao, Y., Ji, C., Guo, X. A transcribed ultraconserved noncoding RNA, uc.417, serves as a negative regulator of brown adipose tissue thermogenesis. FASEB J. 30, 4301–4312 (2016). www.fasebj.org